Identifikasi Miskonsepsi Calon Guru IPA pada Materi Kelistrikan Menggunakan Metode Three-Tier Multiple Choice - Haryanto, Linda Yuni; Nikmah, Zahra Awwalun; Anggraini, Saskia Nazwa; Fauziah, Izzatul; Setyo, Dody Rahayu (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to identify prospective science teachers' misconceptions on electricity using a three-tier multiple-choice test. The research method used is descriptive quantitative with 21 students of the Science Education study program at UIN Sunan Kudus as the subjects. This study was conducted at the Science Education Study Program at UIN Sunan Kudus in the even semester of the 2024/2025 academic year. The subjects consisted of 21 science students at UIN Sunan Kudus. The data collection technique used a Three-Tier Multiple Choice (TTMC) diagnostic test, a three-tier multiple choice instrument used to identify students' understanding and conceptual errors. This test consists of three levels: answers, reasons, and confidence levels in providing answers. The results showed that conceptual understanding and misconceptions were approximately 35% and 30%, respectively. Meanwhile, positive misconceptions and negative misconceptions were approximately 15–18%. This means that approximately 50% of respondents experienced misconceptions on the concepts of series and parallel circuits, electric charge, and electricity sources. Researchers used deeper identification through the second and third tiers to differentiate between misconceptions, positive misconceptions, negative misconceptions, not understanding the concept, not understanding the concept, guessing, and understanding the concept. These findings also confirm that the three-tier multiple-choice method is effective in identifying misconceptions among prospective science teachers.